2005
DOI: 10.1897/05-116r.1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo bioassay‐guided fractionation of marine sediment extracts from the Southern California Bight, USA, for estrogenic activity

Abstract: The exposure and uptake of environmental estrogenic compounds have been reported in previous studies of demersal flatfish species in the central Southern California Bight (SCB), USA. The objective of this study was to evaluate the estrogenic or feminizing activity of marine sediments from the SCB by using in vivo vitellogenin (VTG) assays in male or juvenile fish. In 2003, sediments were collected near wastewater outfalls serving the counties of Los Angeles (LACSD) and Orange (OCSD), and the city of San Diego … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
51
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 35 publications
3
51
0
Order By: Relevance
“…7,8 Due to the concerns of possible impacts of EDCs on aquatic organisms, investigations on these chemicals in the sewage treatment plants, receiving water, and sediments have been carried out in some regions of the world. [9][10][11][12][13][14] High detection frequencies of these EDCs are recorded in aquatic environments, with concentrations ranging from a few parts per trillion to several parts per million. In parallel with chemical analysis, in vivo or in vitro bioassays are often used to screen the estrogenic potency of the environmental samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Due to the concerns of possible impacts of EDCs on aquatic organisms, investigations on these chemicals in the sewage treatment plants, receiving water, and sediments have been carried out in some regions of the world. [9][10][11][12][13][14] High detection frequencies of these EDCs are recorded in aquatic environments, with concentrations ranging from a few parts per trillion to several parts per million. In parallel with chemical analysis, in vivo or in vitro bioassays are often used to screen the estrogenic potency of the environmental samples.…”
Section: Introductionmentioning
confidence: 99%
“…11,12,[38][39][40][41] Obviously, the concentrations of the EDCs in sediments of the Pearl River system (especially the Shijing River) were generally higher than those in other regions of the world. The maximum concentrations in the sediments of the Shijing River were 10-40-fold higher than the reported maximum concentrations in sediments of other regions.…”
mentioning
confidence: 99%
“…It is reported that BP-3 showed hormonal activities (estrogenic, antiestrogenic, androgenic, and antiandrogenic) in fish in both in vitro and in vivo tests [7][8][9]. In male medaka and male California halibut BP-3 lead to vitellogenin induction [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…E2 concentrations in sediments around the outfall were roughly 3-fold higher than those at a reference location (0.45 ng/g vs. 0.16 ng/g dry weight), where no correlation between plasma E2 levels and DNA damage was demonstrated (Schlenk et al, 2005). Mammalian cytochrome P450 1B1 catalyzes production of 4-hydroxy estradiol, which is further metabolized to semiquinones and quinones causing oxidative DNA damage due to redox cycling (Han and Liehr, 1994).…”
mentioning
confidence: 99%